ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KOTA MALANG TAHUN ANGGARAN 2007-2011 - Puspitasari, Ayu Febriyanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The study was conducted to analyze the financial performance of the local government of Malang City in last five years (2007-2011) with a ratio analysis of financial independence, effectiveness and efficiency of the PAD, the ratio of routine expenditure to total expenditure, the ratio of development expenditure to total expenditure, growth ratios, as well as aspects of the analysis financing. Keyword : Financial performance, Ratio Analysis, APBD, Malang City, Revenue, Expenditure, Financing